Therapeutic Potential of Glutamine Pathway in Lung Cancer - Tang, Enyu; Liu, Siyang; Zhang, Zhiming; Zhang, Rixin; Huang, Dejing; Gao, Tong; Zhang, Tianze; Xu, Guangquan (Frontiers in Oncology, 2022)
Cancer cells tend to obtain the substances needed for their development depending on altering metabolic characteristics. Among the reorganized metabolic pathways, Glutamine pathway, reprogrammed to be involved in the physiological process including energy supply, biosynthesis and redox homeostasis, occupies an irreplaceable role in tumor cells and has become a hot topic in recent years. Lung cancer currently maintains a high morbidity and mortality rate among all types of tumors and has been a health challenge that researchers have longed to overcome. Therefore, this study aimed to clarify the essential role of glutamine pathway played in the metabolism of lung cancer and its potential therapeutic value in the interventions of lung cancer.